A força oculta: um estudo sobre a causalidade em hume - FERREIRA, Ian Nascimento (2009)
The goal of this dissertation is to follow the discussion about causation on David Hume s philosophy. First, I try to show how such concept was treated by previous philosophers that might somehow have influenced Hume. I then analyze his contribution to the subject up to the point in which he introduces the idea of necessary connection. The final part of the work is aimed at studying the most important interpretative branches that try to make sense of Hume s ambiguous statements about necessary connection, and the implications the correct understanding of this concept has for his theory of causation